Application of BIM Technology in Bridge Engineering and Obstacle Research. Issue 1 (June 2021) - Huang, Zixing; Tu, Chao; Li, Gen
Abstract: with the development of economy and the reform of cities, the bridge engineering in China has entered a period of rapid development. By 2009, the number of highway bridges in China has exceeded that of the rest of the world. According to the statistics of 2014, the number of roads and bridges in China is 757100, and its extension meters reach 42.5789 million. The emergence of BIM technology has brought a new experience to China's construction industry. Compared with the traditional CAD, the most significant change in BIM technology is to change building information from two-dimensional to three-dimensional. At the same time, BIM visualization, synergy and automation help building participants to do a lot of work better and more conveniently. Because of the continuous expansion of bridge engineering in China, bridge engineering has gradually become more complex and diverse, which has also brought problems to many industries. The research on BIM in our country is still in some surface stages. There are deeper things worth digging into.